PJMHS 2022
DOI: 10.53350/pjmhs20221612545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Methods of Induction of Labour Methods; Khyber Pakhtunkhwa Perspective

Abstract: Objectives: to compare the mechanical, pharmacological or combination of both in induction of labour. Methods: This comparative observational study was conducted in Department of Obs and Gynae, Lady Reading Hospital, from January 2019 to December 2019. In this study all women presenting to labor room with singleton pregnancy and gestational age > 37 weeks and admitted for induction of labor were included. All those women with multiple pregnancies, premature rupture of membrane, malpresentation, and prior Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…21 A recent study comparing four different types of induction showed that foley catheter with or without PGE2 is less effective as compared to PGE2 alone in achieving vaginal delivery as well well as induction to delivery interval. 22 This is in contrast to our study findings. The plausible explanation for this might be that the previous study included patients with previous c-sections in which usually mechanical induction is done and the threshold for repeat c-section in a scarred uterus is usually low.…”
Section: Discussioncontrasting
confidence: 99%
“…21 A recent study comparing four different types of induction showed that foley catheter with or without PGE2 is less effective as compared to PGE2 alone in achieving vaginal delivery as well well as induction to delivery interval. 22 This is in contrast to our study findings. The plausible explanation for this might be that the previous study included patients with previous c-sections in which usually mechanical induction is done and the threshold for repeat c-section in a scarred uterus is usually low.…”
Section: Discussioncontrasting
confidence: 99%